Identification and SAR exploration of a novel series of Legumain inhibitors. Issue 12 (15th June 2019) - Eddie, Sharon L.; Gregson, Aaron; Graham, Emma; Burton, Stephanie; Harrison, Timothy; Burden, Roberta; Scott, Christopher J.; Mullan, Paul B.; Williams, Rich
Graphical abstract: Abstract: This letter describes the development of a series of potent and selective small molecule Legumain inhibitors suitable as chemical probes for in vitro experiments. Our previous research had identified a dipeptide inhibitor utilizing a semi-reversible cyano warhead that generated 2, a cell active inhibitor. This work explores an alternative P2-P3 linker and further SAR exploration of the P3 group which led to the identification of 16i, a highly potent inhibitor with excellent physiochemical properties.